Synthesis of nitrogenated scaffolds derived from fluorene by a modified Ullmann type reaction - Mangione, Maria Ines (2014)
Two novel aromatic molecules were synthesized via a modified Ullmann coupling starting from a known compound 2,7-diiodofluorenone with carbazole derivatives. These compounds were obtained in very good yields. Due to their fluorophore components, like fluorenone and carbazole, they could be applied as scaffolds for the development of organic materials like dendrimers and polymers.